2013
DOI: 10.1016/s0020-1383(13)70210-9
|View full text |Cite
|
Sign up to set email alerts
|

Trends in prevalence, knowledge, attitudes, and practices of helmet use in Cambodia: results from a two year study

Abstract: Introduction Road traffic injuries (RTIs) are a major cause of both morbidity and mortality globally. Relative to countries with similar economic patterns both within and outside of South-East Asia, Cambodia's road traffic fatality rate is high, with motorcyclists accounting for more than half of all fatalities as a result of head injuries. Despite the initiation of national motorcycle helmet legislation for Cambodian drivers in 2009, helmet use among both drivers and passengers remains low. Methods This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“… 7 In addition to the high rate of mortality, the morbidity of motorcycle drivers from traffic accidents are considerably higher when compared to car drivers. 5 This is because not only the safety of the motorcycles are lower than cars, but also many motorcycle drivers do not wear crash helmets 7 , 22 despite the fact that the risk of fatality from a crash is increased among motorcycle drivers who do not wear a crash helmet. 23 …”
Section: Discussionmentioning
confidence: 99%
“… 7 In addition to the high rate of mortality, the morbidity of motorcycle drivers from traffic accidents are considerably higher when compared to car drivers. 5 This is because not only the safety of the motorcycles are lower than cars, but also many motorcycle drivers do not wear crash helmets 7 , 22 despite the fact that the risk of fatality from a crash is increased among motorcycle drivers who do not wear a crash helmet. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found that theories such as the Health Belief Model, Locus of Control, and the Theory of Planned Behavior can help to explain why riders use motorcycle helmets (Aghamolaei, Tavafian, & Madani, 2011, Özkan, Lajunen, Doğruyol, Yıldırım, & Çoymak, 2012. Social norms and attitudes towards helmet use have also been found to have an influence on use rates (Bachani et al, 2013;Haqverdi, Seyedabrishami, Groeger, 2015;Li, Li, Cai, Zhang, & Lo, 2008). Since this study uses an observation based data collection framework, subjective variables that could potentially help to explain variance in helmet use were not assessed.…”
Section: Factors Influencing Helmet Usementioning
confidence: 99%
“…Road safety in BRICS needs to be improved through investment in interventions targeted at the key risk factors and collection of more reliable data to establish baseline values and track temporal changes in more detail. [22][23][24][25] There needs to be regular, large-scale systematic monitoring of the factors that influence road safety. This would then allow the cost-effectiveness of interventions for the improvement of road safety to be rigorously assessed and any temporal changes in road safety to be detected rapidly.…”
Section: Resultsmentioning
confidence: 99%